Weight gain following subthalamic nucleus deep brain stimulation: A PET study. Issue 14 (7th November 2014) - Sauleau, Paul; Le Jeune, Florence; Drapier, Sophie; Houvenaghel, Jean‐François; Dondaine, Thibaut; Haegelen, Claire; Lalys, Florent; Robert, Gabriel; Drapier, Dominique; Vérin, Marc
Abstract Several hypotheses have been put forward to explain weight gain after deep brain stimulation (DBS), but none provides a fully satisfactory account of this adverse effect. We analyzed the correlation between changes in brain metabolism (using positron emission tomography [PET] imaging) and weight gain after bilateral subthalamic nucleus DBS in patients with Parkinson's disease. Body mass index was calculated and brain activity prospectively measured using 2‐deoxy‐2[18F]fluoro‐D‐glucose 3 months before and 4 months after the start of subthalamic nucleus deep brain stimulation in 23 patients with Parkinson's disease. Motor complications (United Parkinson's Disease Rating Scale [UPDRS]‐IV scores) and dopaminergic medication were included in the analysis to control for their possible influence on brain metabolism. Mean ± standard deviation (SD) body mass index increased significantly by 0.8 ± 1.5 kg/m2 (P = 0.03). Correlations were found between weight gain and changes in brain metabolism in limbic and associative areas, including the orbitofrontal cortex (Brodmann areas [BAs] 10 and 11), lateral and medial parts of the temporal lobe (BAs 20, 21, 22, 39 and 42), anterior cingulate cortex (BA 32), and retrosplenial cortex (BA 30). However, we found no correlation between weight gain and metabolic changes in sensorimotor areas. These findings suggest that changes in associative and limbic processes contribute to weight gain after subthalamic nucleus DBS in Parkinson's disease. © 2014 International Parkinson and Movement Disorder Society